Complete plastid genome of Apostasia shenzhenica (Orchidaceae). Issue 1 (2nd January 2019) - Li, Yunxia; Li, Zhanghai; Hu, Qinglin; Zhai, Junwen; Liu, Zhongjian; Wu, Shasha
Abstract: Apostasia shenzhenica is a terrestrial orchid, which belongs to Apostasioideae (Orchidaceae). Here, we determined the complete plastid genome of A . shenzhenica using the Illumina reads in an effort to provide genomic resources useful for its conservation and evolutionary biology study. It has a circular molecular length of 153, 164 bp and contained 109 genes, including 75 protein-coding genes, 4 rRNA genes, and 30 tRNA genes. Phylogenetic analysis indicated that A . shenzhenica was closely related to A . wallichii and embedded in Apostasioideae.